A high-throughput screening for inhibitors of riboflavin synthase identifies novel antimicrobial compounds to treat brucellosis - Serer, María Inés (2019)
Brucella spp. are pathogenic intracellular Gram‐negative bacteria adapted to life within cells of several mammals, including humans. These bacteria are the causative agent of brucellosis, one of the zoonotic infections with the highest incidence in the world and for which a human vaccine is still unavailable. Current therapeutic treatments against brucellosis are based on the combination of two or more antibiotics for prolonged periods, which may lead to antibiotic resistance in the population. Riboflavin (vitamin B2) is biosynthesized by microorganisms and plants but mammals, including humans, must obtain it from dietary sources. Owing to the absence of the riboflavin biosynthetic enzymes in animals, this pathway is nowadays regarded as a rich resource of targets for the development of new antimicrobial agents. In this work, we describe a high‐throughput screening approach to identify inhibitors of the enzymatic activity of riboflavin synthase, the last enzyme in this pathway. We also provide evidence for their subsequent validation as potential drug candidates in an in vitro brucellosis infection model. From an initial set of 44 000 highly diverse low molecular weight compounds with drug‐like properties, we were able to identify ten molecules with 50% inhibitory concentrations in the low micromolar range. Further Brucella culture and intramacrophagic replication experiments showed that the most effective bactericidal compounds share a 2‐Phenylamidazo[2,1‐b][1,3]benzothiazole chemical scaffold. Altogether, these findings set up the basis for the subsequent lead optimization process and represent a promising advancement in the pursuit of novel and effective antimicrobial compounds against brucellosis.